2011
DOI: 10.1080/1059924x.2011.581534
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Hantavirus Infection in Farm and Abattoir Workers in Trinidad—A Preliminary Study

Abstract: Hantaviruses are established causative agents of hemorrhagic fevers and renal diseases amongst other clinical manifestations in humans, with most diagnosis based on serological assays. The disease, which is rodent-borne, has been reported in numerous countries worldwide but information about the disease is scanty in the Caribbean. The objective of this investigation is to determine the frequency of exposure to hantaviruses in a selected apparently healthy human population associated with abattoirs and livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Prevalence of the seropositive status ranged from zero cases [51,55], to 30.6% in a more recent survey from Sweden [31]. When the prevalence rates were broken down by geographic areas, they ranged from 3.0% (0.9-9.2) in eight estimates from the New World [16][17][18]26,27,34,51,52], 3.0% (1.5-6.2) in 14 estimates from European countries [15,[21][22][23][24][25]30,31,35,36,49,50,53,55], to 7.1% (3.2-14.8) in two studies from Western Africa [19,20], and eventually 7.4% (3.0-17.0) in four estimates from Asian Countries [28,29,33]. When estimates for New World were dichotomized for North vs. Central and South America, seroprevalence rates were 1.2% (0.4-3.6) and 4.5% (1.3-14.1), respectively (data not shown in Figure 2).…”
Section: Studies On Agricultural Workersmentioning
confidence: 97%
“…Prevalence of the seropositive status ranged from zero cases [51,55], to 30.6% in a more recent survey from Sweden [31]. When the prevalence rates were broken down by geographic areas, they ranged from 3.0% (0.9-9.2) in eight estimates from the New World [16][17][18]26,27,34,51,52], 3.0% (1.5-6.2) in 14 estimates from European countries [15,[21][22][23][24][25]30,31,35,36,49,50,53,55], to 7.1% (3.2-14.8) in two studies from Western Africa [19,20], and eventually 7.4% (3.0-17.0) in four estimates from Asian Countries [28,29,33]. When estimates for New World were dichotomized for North vs. Central and South America, seroprevalence rates were 1.2% (0.4-3.6) and 4.5% (1.3-14.1), respectively (data not shown in Figure 2).…”
Section: Studies On Agricultural Workersmentioning
confidence: 97%
“…23,24 Antibodies to hantaviruses were not detected in any of the samples analyzed in this study; this is in contrast to a recent study that showed significant exposure rates among farm and abattoir workers in Trinidad. 25 Further investigations to evaluate the risk for hantavirus infection in the Caribbean are thus warranted.…”
Section: Discussionmentioning
confidence: 99%
“…including SEOV, HTNV, PUUV, DOBV, and SNV. In the Caribbean serological and molecular evidence of hantavirus transmission exists for Grenada, Trinidad and Cuba (Sin Nombre strain positive by RT-PCR) however no extensive epidemiological data on hantavirus infection exists for the Caribbean [27,28,29,30]. Recent hantavirus outbreaks in adjacent regions including 4 fatal HPS cases observed in French Guiana (Maripa virus) in 2016 enhance the risk of new and more lethal hantavirus strains entering the Caribbean region via trade and travel [31].…”
Section: Introductionmentioning
confidence: 99%